The crystal structure of plasma gelsolin: implications for actin severing, capping, and nucleation. - Burtnick, L; Koepf, E; Grimes, J; Jones, E; Stuart, D; McLaughlin, P; Robinson, R (1997)
The structure of gelsolin has been determined by crystallography and comprises six structurally related domains that, in a Ca2+-free environment, pack together to form a compact globular structure in which the putative actin-binding sequences are not sufficiently exposed to enable binding to occur. We propose that binding Ca2+ can release the connections that join the N- and C-terminal halves of gelsolin, enabling each half to bind actin relatively independently. Domain shifts are proposed in response to Ca2+ as bases for models of how gelsolin acts to sever, cap, or nucleate F-actin filaments. The structure also invites discussion of polyphosphoinositide binding to segment 2 and suggests how mutation at Asp-187 could initiate a series of events that lead to deposition of amyloid plaques, as observed in victims of familial amyloidosis (Finnish type).